Report(RIGS15-088-0088): Quality of life assessment in head and neck cancer survivors: a follow-up study in East Coast Of Malaysia - Mohamed Ludin, Salizar; Che Abdullah, Che Azunie (2017)
Introduction: Head and neck cancer is the fifth most common cancer in Malaysia. Head and neck cancer survivors have potential negative effects of the tumour itself and its treatment on various functions such as swallowing, speaking, tasting, and smiling as well as on their appearance which will affect their quality of life. It also may lead to facial deformities or permanent changes in speech and expression which can effect social and emotional. Studies conclude that the complications after chemo-radiotherapy effect head and neck cancer survivor physically, psychologically and emotionally. Despite all the issues, quality of life of treatable head and neck cancer patients is unknown. Aim: This study aims to measure the quality of life of treatable head and neck cancer patients before treatment and after 6 months of treatment. Methods: In this study, a cohort study will be employed to fundamentally look into the actual situation of the head and neck cancer survivors’ quality of life. The sample will be those from Ear, Nose & Throat (ENT) clinic and dental clinic of 2 hospitals in East Coast Malaysia. Survey was done before and after 6 months of treatment using questionnaire quality-of-life cancer SURVIVOR (QOL-CS) and Quality-of-Life-Questionnaire-Head & Neck 35 (QLQ-H&N35). Semi-structured interview will be done by using recorder tape in each visit. Results: The mean age of cancer detection was at 53 years, male (65%), married (85%) and squamous cell carcinoma being the most common (80%). Pharynx/ larynx were the most common site of tumour (50%) and surgeries were the most common treatment modality (75%). The mean score of QOL for HNC patient’s post-treatments is 4.84, which is significantly lower than pre-treatments score (6.22). Mean symptoms score for post-treatments is 1.25, lower than pre-treatments score (1.58). Patients experienced substantial decrease in amount of pain killer consumed during post-treatments. In terms of Quality of life of head and neck cancer patients were at medium level but reducing; mean score 6.22 before treatment and 4.84 after treatment. Analysis showed only health history (p-value=0.011<0.05; (p-value=0.012<0.05) was directly significant with the quality of life of HNC patients before and after the treatment. Post-treatment showed only marital status (p-value=0.000<0.05) factor associated with quality of life of HNC patients after the treatment. Conclusion: Quality of life of the patient may reduce after treatment (medium level) and it could be due to underlying illnesses, the effect of other treatment or due to the advancement of cancer.